Blade Breaker - Book 2 - Aveyard, Victoria (New York, NY : HarperTeen, an imprint of HarperCollinsPublishers, 2022)
"Dom, a grieving immortal, strives to fulfill a broken oath. Sorasa, an outcast assassin, faces her past when it returns with sharpened teeth. Valtik, an old sorceress, summons a mighty power. And Corayne, a pirates daughter with an ancient magic in her blood, steps closer to becoming the hero shes destined to be. Together they must assemble an army to face Queen Erida and Taristans wicked forces. But something deadly waits in the shadows, something that might consume the world before theres any hope for victory"--
Keywords: Imaginary wars and battles -- Fiction; Assassins -- Fiction; Good and evil -- Fiction; Wizards -- Fiction; Magic -- Fiction; Fantasy fiction